2012
DOI: 10.1088/0004-637x/754/1/61
|View full text |Cite
|
Sign up to set email alerts
|

Integral Field Spectroscopy and Multi-Wavelength Imaging of the Nearby Spiral Galaxy NGC 5668: An Unusual Flattening in Metallicity Gradient

Abstract: We present the analysis of the full bi-dimensional optical spectral cube of the nearby spiral galaxy NGC 5668, observed with the PPAK IFU at the Calar Alto observatory 3.5m telescope. We make use of broad-band imaging to provide further constraints on the evolutionary history of the galaxy. This dataset will allow us to improve our understanding of the mechanisms that drive the evolution of disks. We investigated the properties of 62 H II regions and concentric rings in NGC 5668 and derived maps in ionized-gas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 144 publications
(189 reference statements)
14
42
0
Order By: Relevance
“…This change in the slope of the radial gradient of oxygen abundance has been reported by several authors (e.g. Bresolin et al 2009;Marino et al 2012;Bresolin et al 2012). If true, migration is an efficient mechanism to intermix the gas and stellar population properties of galaxies, and even to enrich the intergalactic medium (Sánchez-Blázquez et al 2009, for a different explanation to the surface-brightness truncation).…”
Section: Radial Gradientssupporting
confidence: 71%
See 2 more Smart Citations
“…This change in the slope of the radial gradient of oxygen abundance has been reported by several authors (e.g. Bresolin et al 2009;Marino et al 2012;Bresolin et al 2012). If true, migration is an efficient mechanism to intermix the gas and stellar population properties of galaxies, and even to enrich the intergalactic medium (Sánchez-Blázquez et al 2009, for a different explanation to the surface-brightness truncation).…”
Section: Radial Gradientssupporting
confidence: 71%
“…Finally, only those H ii regions with measured Hβ emission line detected at >3σ significance were considered for further analysis (e.g. Marino et al 2012), although they were not masked out and their spectra were not set to zero. This criteria was included to consider only those regions with good line diagnostic ratios and well defined Balmer ratio, both required in further analysis.…”
Section: Deriving the Main Properties Of The Emission Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recently it has been found that some spiral galaxies show lower (higher) oxygen abundance val-ues in the inner (outer) regions than that expected according to the observed negative gradients. This results in a nearly flat distribution or even a drop towards the centre (Belley & Roy 1992;Rosales-Ortega et al 2011;Sánchez et al 2012bSánchez et al , 2014Sánchez-Menguiano et al 2016b;Zinchenko et al 2016), and an abundance flattening or even an increase in the outermost parts (Martin & Roy 1995;Vilchez & Esteban 1996;Roy & Walsh 1997;van Zee et al 1998;Rosales-Ortega et al 2011;Bresolin et al 2012;Marino et al 2012;López-Sánchez et al 2015;Sánchez-Menguiano et al 2016b;Belfiore et al 2017).…”
Section: The Shape Of the Abundance Profilesmentioning
confidence: 99%
“…Peimbert 1979;Shaver et al 1983;Vila-Costas & Edmunds 1992;Zaritsky et al 1994;Kennicutt et al 2003;Pilyugin et al 2004;Bresolin et al 2009b;Rosales-Ortega et al 2011;Marino et al 2012;Sánchez et al 2012b;Pilyugin et al 2014;Sánchez et al 2014;Sánchez-Menguiano et al 2016b;Zinchenko et al 2016;Belfiore et al 2017). However, recently it has been found that some spiral galaxies show lower (higher) oxygen abundance val-ues in the inner (outer) regions than that expected according to the observed negative gradients.…”
Section: The Shape Of the Abundance Profilesmentioning
confidence: 99%